The corporate contract in changing times : is the law keeping up? - Corporate Contract in Changing Times: Is the Law Keeping Up (Conference) (2016); Davidoff Solomon, Steven, 1970-; Thomas, Randall S., 1955- (Chicago : The University of Chicago Press, 2019)
Over the past few decades, significant changes have occurred across capital markets. Shareholder activists have become more prominent, institutional investors have begun to wield more power, and intermediaries like investment advisory firms have greatly increased their influence. These changes to the economic environment in which corporations operate have outpaced changes in basic corporate law and left corporations uncertain of how to respond to the new dynamics and adhere to their fiduciary duties to stockholders. Steven Davidoff Solomon and Randall Stuart Thomas bring together leading corporate law scholars, judges, and lawyers from top corporate law firms to explore what needs to change and what has prevented reform thus far.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 23, 2019).
Keywords: Corporation law -- United States -- Congresses; Law; Laws of specific jurisdictions & specific areas of law